Microsporidia—Emergent pathogens in the global food chain - Stentiford, G.D.; Becnel, J.J.; Weiss, L.M.; Keeling, P.J.; Didier, E.S.; Williams, B.A.P.; Bjornson, S.; Kent, M.L.; Freeman, M.A.; Brown, M.J.F.; Troemel, E.R.; Roesel, Kristina; et al. (Elsevier, 2016)
Intensification of food production has the potential to drive increased disease prevalence in food plants and animals. Microsporidia are diversely distributed, opportunistic, and density-dependent parasites infecting hosts from almost all known animal taxa. They are frequent in highly managed aquatic and terrestrial hosts, many of which are vulnerable to epizootics, and all of which are crucial for the stability of the animal–human food chain. Mass rearing and changes in global climate may exacerbate disease and more efficient transmission of parasites in stressed or immune-deficient hosts. Further, human microsporidiosis appears to be adventitious and primarily associated with an increasing community of immune-deficient individuals. Taken together, strong evidence exists for an increasing prevalence of microsporidiosis in animals and humans, and for sharing of pathogens across hosts and biomes.